Numerical Simulation Analysis of Wood/PP Composites for Injection-Moulded Car Battery Trays - Razak, Zakaria; Bakar Sulong, Abu; Muhamad, Norhamidi; Khairul Fadzly Md Radzi, Mohd.; Farhani Ismail, Nur; Tholibon, Dulina; Tharazi, Izdihar (International Journal of Engineering and Technology, 2018)
This research focused on the simulation analysis of wood polymer composites (WPCs) based on polypropylene (PP) for the injection moulding of automotive parts, namely car battery trays (CBTs). A plastic CBT, which is commonly used to support the battery in a car engine, is manufactured completely through the injection moulding process. The conventional design method is clearly unable to satisfy production requirements; however, with the application of the Moldflow software rational production process parameters, the filling time, injection pressure, clamping force, and others, can be formulated. A moulded CBT was designed using a computer-aided design tool, namely CatiaV5R20, before being imported to the finite element analysis tool, Moldflow. The use of the Moldflow software enabled a full analysis to be conducted of the material flow inside the mould cavity for the moulded CBT. Two types of gates, namely, the sprue and pinpoint gates, were used, through which the analyses were carried out by the Moldflow software to check the filling time, injection pressure, clamping force and warpage, by simulation in the sequential trials. The data on the wood fibre/PP composite, where 40 wt% of wood fibre loading was used. Finally, the use of the Moldflow simulation software was presented.Â Â